The Influence of Service Quality, Price, Facilities, and Security on Customer Satisfaction of TransJakarta Bus Services - Herawati, Lisda; Putri, Liestyaningrum Rahmadhani Wisnu (Golden Ratio of Mapping Idea and Literature Format, 2026)
Customer satisfaction is a crucial indicator of public transportation service performance. For TransJakarta buses, satisfaction is shaped by service quality, price, facilities, and safety. This study aims to analyze the influence of these four variables on customer satisfaction, examining both partial and simultaneous effects. A quantitative approach was used with explanatory research methods. Data were collected through a Likert scale questionnaire (1–5) distributed to 200 TransJakarta bus users in the DKI Jakarta area. The analysis techniques included validity and reliability tests, classical assumptions, multiple linear regression, t-tests, F-tests, and the coefficient of determination (Adjusted R²). The results indicate that price, facilities, and safety have a significant impact on customer satisfaction, whereas service quality does not exhibit a significant influence. Simultaneously, the four variables significantly influence customer satisfaction with a model contribution of 51.2% to the variability of satisfaction. These findings underscore the importance of implementing competitive fare management policies, enhancing facility quality, and strengthening the security system to maintain and enhance customer loyalty. Practically, this study encourages TransJakarta management to prioritize price, facilities, and safety as strategies for service improvement. Theoretically, the results contribute to transportation service management literature by showing that, in low-cost public transport contexts, price and facilities may exert greater influence on satisfaction than service quality.